Phân tích đa thức thành nhân tử :
\(x^4+x^2+1\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
x⁸ + x⁴ + 1
= x⁸ + 2x⁴ + 1 - x⁴
= (x⁴ + 1)² - x⁴
= (x⁴ + 1)² - (x²)²
= (x⁴ + 1 + x²)(x⁴ + 1 - x²)
= (x⁴ + x² + 1)(x⁴ - x² + 1)
e: \(x^4-2x^3+x^2\)
\(=x^2\cdot x^2-x^2\cdot2x+x^2\cdot1\)
\(=x^2\left(x^2-2x+1\right)\)
\(=x^2\left(x-1\right)^2\)
f: \(27y^3-x^3\)
\(=\left(3y\right)^3-x^3\)
\(=\left(3y-x\right)\left(9y^2+3xy+x^2\right)\)
a) ( x 2 – 4x + 1)( x 2 – 2x + 3). b) (3x – y – 1)(x – 7y – 1).
a) \(\left(x^2-7x+12\right).\left(x^2-15x+56\right)-60\)
\(=\left(x-3\right)\left(x-4\right)\left(x-7\right)\left(x-8\right)-60\)
b) \(x^4+2000x^2+1999x+2000\)
\(=\left(x^2-x+2000\right)\left(x^2+x+1\right)\)
\(=\left(x^2+x-1\right)^2+1999\left(x^2+x+1\right)+1\)
1/(x+2)2 -(3x-1)2=(x+2+3x-1)(x+2-3x+1)=4x(-2x+3)=-8x2+12x
2/(x4+x2)(-2x3-2x)=x2(x2+1)-2x(x2+1)=(x2+1)(x2-2x)
\(x^4-y^4+2x^3y-2xy^3\)
\(=\left(x^2+y^2\right)\left(x^2-y^2\right)+2xy\left(x^2-y^2\right)\)
\(=\left(x^2-y^2\right)\left(x^2+y^2+2xy\right)\)
\(=\left(x-y\right)\left(x+y\right)\left(x+y\right)^2\)
\(=\left(x-y\right)\left(x+y\right)^3\)
\(x^4-y^4+2x^3y-2xy^3\\ =\left(x^2\right)^2-\left(y^2\right)^2+2xy\left(x^2-y^2\right)\\ =\left(x^2-y^2\right)\left(x^2+y^2\right)+2xy\left(x^2-y^2\right)\\ =\left(x^2-y^2\right)\left(x^2+y^2+2xy\right)\\ =\left(x-y\right)\left(x+y\right)\left(x+y\right)^2\\ =\left(x-y\right)\left(x+y\right)^3\)
b) \(25-x^2+14xy-49y^2\)
\(=25-\left(x^2-14xy+49y^2\right)\)
\(=25-\left[x^2-2\cdot7y\cdot x+\left(7y\right)^2\right]\)
\(=25-\left(x-7y\right)^2\)
\(=5^2-\left(x-7y\right)^2\)
\(=\left[5-\left(x-7y\right)\right]\left[5+\left(x-7y\right)\right]\)
\(=\left(5-x+7y\right)\left(5+x-7y\right)\)
c) \(x^5+x^4+1\)
\(=x^5+x^4+1+x^3-x^3\)
\(=\left(x^5+x^4+x^3\right)+\left(1-x^3\right)\)
\(=x^3\left(x^2+x+1\right)+\left(1-x\right)\left(x^2+x+1\right)\)
\(=\left(x^2+x+1\right)\left[x^3+\left(1-x\right)\right]\)
\(=\left(x^2+x+1\right)\left(x^3+1-x\right)\)
b: 25-x^2+14xy-49y^2
=25-(x-7y)^2
=(5-x+7y)(5+x-7y)
c: =x^5+x^4+x^3+1-x^3
=x^3(x^2+x+1)+(1-x)(x^2+x+1)
=(x^2+x+1)(x^3+1-x)
\(x^4+x^2+1\)
\(=x^4+2x^2+1-x^2\)
\(=\left(x^2+1\right)^2-x^2\)
\(=\left(x^2+1+x^2\right)\left(x^2+1-x^2\right)\)
\(=2x^2+1\)